Development of non-equiatomic Bio-HEAs based on TiZrNbTa-(Mo and Mn) - Torrento, Jhuliene Elen [UNESP]; Sousa, Tiago Dos Santos Pereira De [UNESP]; Cristino Da Cruz, Nilson [UNESP]; Santos De Almeida, Gerson [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Grandini, Carlos Roberto [UNESP]; Nespeque Correa, Diego Rafael (AIP Publishing, 2022)
This study produced non-equiatomic TiNbZrTaMn and TiNbZrTaMo high entropy alloy (HEAs) by argon arc-melting and heat-treated for microstructural homogenization. The phase composition, microstructure, and selected mechanical properties were measured and compared with theoretical predictions. Additionally, electrochemical and cytotoxicity tests evaluated their potential applicability for use as biomaterials. X-ray diffraction measurements patterns showed a single BCC phase for the TiNbZrTaMn and a secondary HCP phase for the TiNbZrTaMo sample. The microstructural analysis revealed the formation of irregular grain boundaries and some lamellae formation, with chemical segregation of the alloying elements at the sub-micro-scale. The samples exhibited elastic modulus (80-110 GPa) closer to CP-Ti grade 2 (100 GPa) and higher Vickers microhardness (450-550 HV) than Ti-6Al-4V alloy (400 HV). The electrochemical and biological tests indicated a superior corrosion resistance against 0.9% NaCl solution compared with commercial metallic biomaterials, with proper cell adhesion and viability of pre-osteoblastic cells and hydrophilic behavior. Altogether, the data indicate that TiNbZrTaMn depicts better applicability potential for being used as a biomaterial in biomedical applications than some commercial materials (SS 316L, CP-Ti grade 2, and Ti-6Al-4V), mainly considering load-bearing orthopedical implants.